PENEGAKAN HUKUM TERHADAP TINDAK PIDANA INFORMASI PALSU YANG MEMBAHAYAKAN KESELAMATAN PENERBANGAN - Rahardjo, Poetoet Sri; Dyahtaryani, Lidia Rina; Sudarto, Sudarto (LITERATUS, 2024)
Aviation safety is a problem that currently requires attention and has become a national and international issue. Because modes of transportation that have fast characteristics are becoming more and more crowded and thus the vulnerability to accidents is increasing. Recently, Indonesia has been one of the countries in the world whose aviation safety problems are very worrying related to criminal acts that endanger aviation safety. Several provisions have been issued by the government by adopting or converting international conventions to issuing specific laws and regulations, however, several regulations and deregulations of laws and regulations which carry criminal threats still contain overlap and are felt to not provide a sense of justice and legal uncertainty. This research aims to understand the regulation of criminal acts of false information that endanger aviation safety and the resolution process by researching and reviewing criminal threat norms regulated in several statutory regulations as well as the authorities in the resolution process. That this research was carried out using normative juridical methods is supported by field data.